Conversion of CO2 to Methanol via photo catalysis routes over nickel-loaded CdS under visible light irradiation - Bakar, N.K.B. (Institute of Physics Publishing, 2020)
The abundance of carbon dioxide gas in the atmosphere raises concerns as it affects the environmental sustainability, human's wellbeing as well as the nature. The photocatalysis conversion of carbon dioxide produces valuable gas and limits environmental issue in the same time. Therefore, it attracts the attention to synthesize photocatalyst that is active under visible light irradiation since sunlight provides abundant photon energy mostly in visible light range. In this study, CdS as visible light-active photocatalyst is loaded with nickel to improve its performance to convert CO2 to methanol under irradiation of 500 W of Xe lamp as visible light source. The spherical nanoparticles morphology can be observed for synthesized CdS and Ni/CdS by using field emission scanning electron microscopy (FE-SEM) analysis. The yield of methanol was examined by using high performance liquid chromatography (HPLC). The result shows that the yield can be improved from 11 Î¼mol/g-catalyst to 2348 Î¼mol/g-catalyst by loading of 3wt of nickel in CdS. The further loading of nickel decreased the yield of methanol. Â© Published under licence by IOP Publishing Ltd.